PENGARUH JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH (Arachis hipogaea L.) - Josina Irene Brigetha Hutubessy (Agriculture Faculty of Flores University, 2012)
This research aims at investigating the influence of planting distance towards growth and yield of peanut and optimal planting distance that can raise the growth of peanut seeds. The method used was Randomized Block Design with treatment as follows: J1 = planting distance 10 cm x 15 cm, J 2 = planting distance 15 cm x 15 cm, J 3 = planting distance 10 cm x 20 cm 4, J = planting distance 15 cm x 20 cm, J 5 planting distance = 10 cm x 30 cm, J 6 = 15 cm x 30 cm. Observation Variables in this study are the height of the plant, a number of leaves, leaf area, leaf area index, Podsnumber/Tan, pods weight/Tan, Seedsnumber /Tan, Fresh Seed Weight/Ha, Dry Seed Weight/Tan, heavy Seed dry/Ha, Fresh maximal yield and residues weight/Tan, dry maximal yield and residue/Ha. The result of this experiment found that the use of distance planting can give a good influence on each variable observation, both on the observation of growth as well as on the yield of peanut.